RBIO-01. PROSPECTIVE OBSERVATIONAL STUDY TO DETERMINE THE IMMUNE SYSTEM RESPONSE TO GAMMA KNIFE RADIOSURGERY FOR VESTIBULAR SCHWANNOMAS. (9th November 2020) - Silverman, Joshua S; Gurewitz, Jason; Gunter, Courtney; Cooper, Benjamin; Palermo, Amy; Boulio, Lynda; Schafrick, Jessica; Lim, Whei Ying; Karhan, Ece; Renzullo, Stephanie; Kozhaya, Lina; Golfinos, John; et al.
Abstract: INTRODUCTION: The effects of radiosurgery for primary intracranial tumors on systemic immune response are unknown. Vestibular schwannomas (VS) treated with Gamma Knife (GK) have high control rates and low risk of adverse effects. This study examines if radiosurgery for VS is associated with an immune response detectable by peripheral blood sampling, and if that response can be correlated with tumoral expansion and/or toxicity. METHODS: 50 patients treated with GK for VS were enrolled on an IRB-approved, prospective study at initial consultation. Blood samples were drawn preceding GK and 6 months and 1 year follow-up. Neurological and hearing outcomes were assessed. Tumor volume was measured at treatment, 6 months, and 1 year follow-up. Tumoral expansion (TE) was defined by volumetric increase >20%. Immunophenotyping via multicolor flow cytometry panels evaluated lymphoid and myeloid differentiation, phenotypic characterization, activation, tissue homing, and immune exhaustion. RESULTS: Median volume at radiosurgery was 0.55cc (range 0.04-11.94) and median margin dose was 12.5Gy (11.5-13) prescribed to the 50% isodose line (50-60). 22 tumors exhibited TE, 20 at six months and 2 at one year. No VS with TE grew at median follow-up of 30.8 months (9.8-52.8). 1 tumor, non-expanding (NE) post-GK, showed progression at 24 months. Presence of cranial neuropathy and hearing decline was similar in both groups. Immunophenotyping showed numerous significant (p< .05) changes in the TE group, not seen in NE, at 6 months and 1 year follow-up compared to baseline. Major changes were observed in cytokine secretion (e.g. IFNg, TNF or IL-17) of CD4+ and CD8+ memory T cells, frequencies of regulatory T cells, increased death of CD8+ effector cells in culture, suggesting chronic activated state. CONCLUSION: Vestibular schwannomas that expand after GK are associated with a peripherally measurable change in systemic immune response that is absent from non-expanding tumors. The biologic underpinnings of these findings require further study.